Potential genetic contributions of the central nervous system to a predisposition to elite athletic traits: State-of-the-art and future perspectives - Kitazawa, H.; Hasegawa, K.; Aruga, D.; Tanaka, M. (Genes, 2021)
Recent remarkable advances in genetic technologies have allowed for the identification of genetic factors potentially related to a predisposition to elite athletic performance. Most of these genetic variants seem to be implicated in musculoskeletal and cardiopulmonary functions. Conversely, it remains unclear whether functions of the central nervous system (CNS) genetically contribute to elite athletic traits, although the CNS plays critical roles in exercise performance. Accumulating evidence has highlighted the emerging implications of CNS-related genes in the modulation of brain activities, including mental performance and motor-related traits, thereby potentially contributing to high levels of exercise performance. In this review, recent advances are summarized, and future research directions are discussed in regard to CNS-related genes with potential roles in a predisposition to elite athletic traits.